2000
DOI: 10.1161/01.hyp.36.2.187
|View full text |Cite
|
Sign up to set email alerts
|

CA-Repeat Polymorphism in Intron 1 of HSD11B2

Abstract: Abstract-Mutations in the HSD11B2 gene encoding the kidney (11-HSD2) isozyme of 11␤-hydroxysteroid dehydrogenase cause apparent mineralocorticoid excess, a form of familial hypertension. Because the hypertension associated with AME is of the salt-sensitive type, it seemed possible that decreases in 11-HSD2 activity might be associated with salt sensitivity. To examine this, Italians with mild hypertension underwent a protocol consisting of a rapid intravenous saline infusion and subsequent furosemide diuresis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 43 publications
5
47
1
2
Order By: Relevance
“…Preliminary data suggest that impaired 11␤HSD2 activity is associated with an increased susceptibility of BP to salt load (38), an observation that is in line with the well-established concept that low-renin hypertension generally is considered a salt-sensitive form of high BP (39). It is interesting that this propensity for increased salt sensitivity in association with decreased activity of the 11␤HSD2 enzyme may be genetically determined by variants in the HSD11B2 promoter or by the presence of undetected mutations in the HSD11B2 gene itself (38,40), an issue that deserves further investigation. This hypothesis is supported by the clinical response in two of our patients (kindred 2 and 3), who showed a good BP response to salt restriction.…”
Section: ␤Hsd2 and Essential Hypertensionsupporting
confidence: 55%
“…Preliminary data suggest that impaired 11␤HSD2 activity is associated with an increased susceptibility of BP to salt load (38), an observation that is in line with the well-established concept that low-renin hypertension generally is considered a salt-sensitive form of high BP (39). It is interesting that this propensity for increased salt sensitivity in association with decreased activity of the 11␤HSD2 enzyme may be genetically determined by variants in the HSD11B2 promoter or by the presence of undetected mutations in the HSD11B2 gene itself (38,40), an issue that deserves further investigation. This hypothesis is supported by the clinical response in two of our patients (kindred 2 and 3), who showed a good BP response to salt restriction.…”
Section: ␤Hsd2 and Essential Hypertensionsupporting
confidence: 55%
“…Research suggests a reduced activity of 11b-hydroxysteroid dehydrogenase type 2 (11b HSD2) in essential hypertension and SS. [8][9][10][11][12] 11b HSD2 converts cortisol into its less active metabolite cortisone. In the case of absence of the enzyme, caused for example by mutations of the HSD11B2 gene, as in the rare syndrome of apparent mineralocorticoid excess, patients show increased tubular sodium retention, hypokalemia and severe hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors 12 did not suggest that HSD2 variants contribute to hypertension, it has been shown that some polymorphisms may be associated with salt-sensitive hypertension. 7,[13][14][15] Other studies searched for functional alterations in renal HSD2 by comparison of urinary excretion of cortisol and its metabolites in normotensive and hypertensive subjects. In some cases, 6,16,17 the 5␤ tetrahydrocortisol (THF) plus 5␣ tetrahydrocortisol (␣THF)/tetrahydrocortisone (THE) or urinary free cortisol (UFF)/urinary free cortisone (UFE) ratios were found slightly elevated in hypertensive patients, while other reports 18,19 indicate no significant change between normotensive and hypertensive subjects.…”
mentioning
confidence: 99%